Roles of end‐binding 1 protein and gamma‐tubulin small complex in cytokinesis and flagella formation of Giardia lamblia - Kim, Juri (John Wiley and Sons Inc., 2018)

(untitled) (Microbiologyopen)
Giardia lamblia is a unicellular organism with two nuclei, a median body, eight flagella, and an adhesive disk. γ‐Tubulin is a microtubule (MT)‐nucleating protein that functions in the γ‐tubulin small complex (γ‐TuSC) in budding yeast. In this study, G. lamblia γ‐tubulin (Glγ‐tubulin) was found to bind to another MT‐binding protein, namely G. lamblia end‐binding protein 1 (GlEB1), via both in vivo and in vitro assays. Hemagglutinin (HA)‐tagged Glγ‐tubulin localized to the basal bodies, axonemes, and median bodies of G. lamblia trophozoites. The knockdown of Glγ‐tubulin expression using an anti‐Glγ‐tubulin morpholino resulted in a decreased growth rate and an increased failed cytokinesis cells of Giardia. The formation of median bodies was affected, and the central pair of MTs in flagella was frequently missing in the Giardia treated with an anti‐Glγ‐tubulin morpholino. G. lamblia γ‐tubulin complex protein 2 (GlGCP2) and GlGCP3, which are putative components of γ‐TuSC, were co‐immunoprecipitated with HA‐tagged Glγ‐tubulin in Giardia extracts. The knockdown of GlGCP2 and GlGCP3 expression also resulted in decreased formation of both the median body and flagella MTs. Knockdown of Glγ‐tubulin, GlGCP2, and GlGCP3 expression affected localization of GlEB1 in G. lamblia. In addition, decreased level of GlEB1 caused reduced formation of median body and the central pair of flagella MTs. These results indicated that Glγ‐tubulin plays a role in MT nucleation for median body formation and flagella biogenesis as a component of Glγ‐TuSC in Giardia and GlEB1 may be involved in this process.